UBER: DOES CORPORATE CULTURE MATTER? - et. al, Dr. Haresh Barot (International Journal of Advanced Science and Technology, 2020)
The case focuses on the unicorn “Uber” and the current issues of contention at the company. The case primarily tries to bring home the importance and the repercussion of and toxic and aggressive culture on the various facets of the organization which could be explicit and implicit. The case also unveils the role played by the top management leadership in setting the tone of conduct for organization. Finally, the case study also presents the compounded impact of the same on an “Employer Brand”.